TEKANAN EKONOMI DAN STRATEGI KOPING KELUARGA PETANI DI DAERAH RAWAN BANJIR - Astuti, Tri Wulandari Henny; Hartoyo, Hartoyo; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2016)
This study aimed to analyze the influence of family characteristics and economic pressure on coping strategies of farmer families in flash flood areas, Kebumen District. Farmer families that involved in the study were 100 families consisting of 50 families from the village of Kemujan and 50 families from the village of Tegalsari. Data were analyzed using descriptive analysis, different t test, and multiple linear regression. Farmer family perceived the economic pressure of their family in the medium category. Economic coping strategies which were done by farmer family are also classified as moderate, but the intensity of coping strategies done by farmer family was categorized into low level. Economic pressure of family increases with the number of family burden and the type of government assistance that has been received. In contrast, the economic pressure decreases as the increase of home-grounds and also the change of ownership status of the house. Economic pressure of family affects the coping strategies both in number and intensity. Another factor that determines coping strategies of family is the age of the husband, the husbands’ side job, and the wife's work. The number and intensity of coping strategies that family has will increase in line with the age of husband and a condition when wife has a job. The number of coping strategies done by family also increases if husband has side job. This research shows the close relationship between economic pressure and coping strategies of farmer family in flash flood areas.